The microbial plankton of Lake Fryxell, southern Victoria Land, Antarctica during the summers of 1992 and 1994 - Laybourn-Parry, Johanna; James, Mark R; McKnight, Diane M; Priscu, John; Spaulding, Sarah A; Shiel, Russell (2023)
Murray-Darling Freshwater Research Centre MDFRC item. Samples collected from Lake Fryxell, southern Victoria Land, Antarctica in January 1992 and 1994 were analysed for the abundance of bacterioplankton and the diversity and abundance of protistan plankton. At the times of sampling, 14 ciliate species and 10 species of autotrophic flagellate were recorded. The samples contained two species of rotifer (Philodina spp.), which formed the first record of planktonic metazoans in the Dry Valley lakes of this region of Antarctica. Bacterial concentrations ranged between 1.0 and 3.8×108 l-1 in the upper oxic waters increasing to 20×108 l-1 in the anoxic waters. Heterotrophic flagellates decreased in abundance down the oxygenated water column, disappearing completely at 9 m, and ranged between 0.28 and 7.39×105 l-1 in abundance. Autotrophic flagellates were much more abundant exhibiting a number of distinct peaks down the water column (1.89–25.3×108 l-1). The ciliated protozoa were very abundant (up to 7720 l-1) in relation to flagellate and bacterial numbers, typical of oligotrophic lakes world-wide. The distribution of the protistan plankton showed marked zonation, probably in response to the differing salinity and temperature gradients in the water column. Possible trophic interactions are discussed and comparisons with other continental Antarctic lakes made.